An evidence based narrative review on treatment of diabetic foot osteomyelitis. Issue 5 (October 2020) - Aicale, Rocco; Cipollaro, Lucio; Esposito, Silvano; Maffulli, Nicola
Abstract: Objective: The diagnosis of diabetic food infection is usually clinical, and its severity is related to location and depth of the lesion, and the presence of necrosis or gangrene. Osteomyelitis of the foot and ankle can be extremely debilitating, and, in the preantibiotic era acute staphylococcal osteomyelitis carried a mortality rate of 50%. The microbiology of diabetic foot osteomyelitis (DFO) is usually polymicrobial. Indeed, gram-negative and gram-positive bacilli can be identified using molecular techniques applied to bone biopsies compared to conventional techniques. The aim of the present study is to report a complete overview regarding medical and surgical management of diabetic foot osteomyelitis (DFO) in combination or alone. Materials and methods: We performed a search in PubMed and Scopus electronic databases (up to January 2019) of articles assessing the epidemiology, diagnostic strategy and pharmacological treatment of diabetic foot infection. In the search strategy, we used various combinations of the following key terms: infection, orthopaedic, diabetic foot, management, DFO. Results: This article discusses the definition, epidemiology, microbiological assessment, clinical evaluation, pharmacological and surgical management and a comparison between them, of DFO. After the initial literature search and removal of duplicate records, a total of 756 potentially relevant citations were identified. After a further screening and according to the inclusion criteria, a total of 65 articles were included in the present review. Conclusion: The association of antibiotic and surgical therapy seems to be more effective compared to each one alone. The lack of comparison studies and randomized controlled trials makes it difficult to give information about the efficacy of the different management therapies.